2019
DOI: 10.1186/s12903-019-0716-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the oral health behavior, knowledge and status among dental and medical undergraduate students: a cross-sectional study

Abstract: BackgroundIt is widely accepted that oral health plays an important role in overall health. Both dental and medical students are expected to possess good oral health awareness and work together for public oral health promotion especially in developing countries like China. The aim of this study was to assess the oral health knowledge, behavior and status of dental and medical undergraduate students in the first (fresh) and third year (before specialized courses) study.MethodsA self-administered structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
4
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 36 publications
6
81
4
12
Order By: Relevance
“…All the students wanted to have clean teeth in university life. The findings of current study were in line with the finding a study conducted in China, where most of the students had proper knowledge and positive behavior about good oral health [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All the students wanted to have clean teeth in university life. The findings of current study were in line with the finding a study conducted in China, where most of the students had proper knowledge and positive behavior about good oral health [14].…”
Section: Discussionsupporting
confidence: 89%
“…Various studies have been conducted to evaluate the knowledge of oral health and oral practices for adults and old people [12][13][14], but still, there is a lack in the literature to evaluate the knowledge and practices of university students. The university students are considered as the most educated people of the community.…”
Section: Introductionmentioning
confidence: 99%
“…Goodarzi et al 12 found that 55.3%% of female students aged 10-12 years brushed at least twice per day, 22.4% used dental floss, and 23% reported a routine dental visit every 6 months. Prevalence of flossing or mouthwash use among dental students is 49.7% in China 18 and that of OHB among schoolchildren 26.7% in Cambodia. 19 The findings of the regression analysis indicated that sex, mother's education, socioeconomic status of households, and oral health literacy (ie, oral health of similar importance to that of rest of body) were the main factors affecting good OHB among schoolchildren.…”
Section: Discussionmentioning
confidence: 99%
“…Muralidharan et al, reported that Indian students having oral hygiene knowledge of topical fluorides was significantly associated with good oral hygiene behavior [14]. Yao et al, reported that dental students in China had better oral hygiene behavior than medical students [15]. Márquez-Arrico et al, reported that use of dental floss was associated with good dental knowledge, however, frequency of tooth brushing did not present significant associations with levels of oral health knowledge in Spanish adult population [30].…”
Section: Plos Onementioning
confidence: 99%
“…In other countries, similar results have been reported [ 12 14 ]. Furthermore, it has been reported that students who had acquired dental knowledge during the university life improved their oral health status [ 15 ].…”
Section: Introductionmentioning
confidence: 99%